Energy Industry using Solar Energy (2019/ Efficient and Cost Saving opportunities in Concrete Manufacturing 2020) - Shaikh Saif, Raju Narwade, Sayed Anwar (International Journal of Advanced Science and Technology, 2020)
Climate change and energy crises are global challenges and it is very much clear that the use of fossil fuels should be limited in the coming period. Energy is considered an important Factor for generation of wealth and a signiﬁcant factor in economic development. Energy consumption in the Construction Sector is the 2nd  Maximum  in our Country.  Our country has setup an green energy target that till march 2022 of 227Gw.Development and promotion of non-conventional/alternate/new and renewable sources of energy such as solar, wind and bio-energy, etc., are also getting sustained attention. Alternative energy source has long predicted that there are fortunes to be made from smart investments in renewable energy from various investors. Solar panels Comes in various materials such as monocrystalline and polycrystalline. Monocrystalline is a bit Expensive but it has 17.% more efficiency then polycrystalline panels . If once installed then this panels have a life of 25-30 years also they are maintenance free for its most life as far as some physical  damage is done to some panel or dust accumulation on then panels proper washing is necessary of the panels to assure optimum level of efficiency is achieved.Keywords: Solar Power Energy, Rmc Industry, Environmental problems, Renewable Energy.